2002
DOI: 10.1076/phbi.40.5.336.8453
|View full text |Cite
|
Sign up to set email alerts
|

Analgesic Properties of Umbellatine from Psychotria umbellata

Abstract: Interesting analgesic activity has been previously identified in alkaloids isolated from the genus Psychotria (Rubiaceae). We here report the analgesic activity of umbellatine, a new glycoside indole monoterpene alkaloid isolated from Psychotria umbellata. Umbellatine produced a dose-dependent (100-300 mg/kg) analgesic effect, partially reversed by naloxone, in the tail-flick and hot-plate models. These results suggest an analgesic effect at least in part associated with the activation of opioid receptors. In … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
27
0

Year Published

2005
2005
2019
2019

Publication Types

Select...
8
2

Relationship

0
10

Authors

Journals

citations
Cited by 41 publications
(27 citation statements)
references
References 18 publications
0
27
0
Order By: Relevance
“…Morphine (morphinan alkaloid) is the most famous example of an alkaloid with analgesic activity and one of the most powerful, showing that this phytochemical class is also rich in constituents with the said action, especially among the indolic alkaloids [489][490][491][492]. Alkaloids isolated from Psychotria colorata show marked naloxone-reversible antinociceptive activity in animals [493].…”
Section: -Memory Enhancersmentioning
confidence: 98%
“…Morphine (morphinan alkaloid) is the most famous example of an alkaloid with analgesic activity and one of the most powerful, showing that this phytochemical class is also rich in constituents with the said action, especially among the indolic alkaloids [489][490][491][492]. Alkaloids isolated from Psychotria colorata show marked naloxone-reversible antinociceptive activity in animals [493].…”
Section: -Memory Enhancersmentioning
confidence: 98%
“…Other work related to P. colorata was carried out by Both et al [51] in order to evaluate the analgesic activity of hodgkinsine (11), a major alkaloid isolated from this plant. The authors concluded that this compound presented dose-dependent analgesic activity in mice, probably mediated by opioid and glutamate receptors, suggesting that it participates in the analgesia previously reported for P. colorata [72].…”
Section: Analgesic Activitymentioning
confidence: 99%
“…Psychollatine, the major MIA isolated from Psychotria umbellata Vell., exhibited mild analgesic effects against a number of algogenic stimuli [15], anxiolytic (7.5 and 15 mg/kg) and antidepressant effects (3 and 7.5 mg/kg) in mice models [16,17]. In higher doses (100 mg/kg), psychollatine impaired the acquisition of learning and memory consolidation [16], suggesting the modulation of different neurotransmitter systems, such as glutamate, opioid and serotonergic pathways.…”
Section: Introductionmentioning
confidence: 98%